Controle genético da resistência à Colletotrichum siamense e associação genômica ampla para resistência à Lasiodiplodia theobromae e Neofusicoccum parvum em Mangifera indica - Aquino, Deisy Aiane Lima de (2021)
Mango (Mangifera indica L.) is an economically and nutritionally important tropical and subtropical fruit crop and anthracnose caused by the fungi Colletotrichum siamense, Lasiodiplodia theobromae and Neofusicoccum parvun is one of the limiting factors in its production. Therefore, the objective of the present study was to select progenies and estimate the inheritance of resistance to anthracnose caused by the fungus Colletotrichum siamense, and to find SNP and microsatellite markers associated with resistance to Neofusicoccum parvum and Lasiodiplodia theobromae in mango trees. In the first study, resistance to anthracnose was evaluated in 'Haden', 'Keitt' and 'Tommy Atkins' cultivars and studied the genetic control of resistance and heritability in populations obtained from crosses between 'Haden' × 'Tommy Atkis' and 'Keitt' × 'Tommy Atkins'. For the evaluation of parental resistance and genetic control in populations, inoculation of the fungus was carried out in the young branches of the plant. For the estimation of the heritability parameter, the mixed model REML / BLUP method was used, as well as the Burton model (BM). For genetic control of resistance, the chi-square test was used in populations. Cultivars ‘Keitt’ and ‘Haden’ were resistant to the fungus C. siamense, while ‘Tommy Atkins’ was moderately susceptible. Resistance to anthracnose is of simple inheritance 15:1 conferred by recessive alleles with epistatic effect, for both ‘Haden’ × ‘Tommy Atkis’ and ‘Keitt’ × ‘Tommy Atkins’ populations. Inheritability by REML/BLUP 88% ‘Haden’ x ‘Tommy Atkins’ and 78% ‘Keitt’ x ‘Tommy Atkins’ and by MB 90%. In the second study, single polymorphism (SNP) and microsatellites data from 95 plants of the 'Haden' × 'Tommy Atkins' population were analyzed by allelic and genotypic association, linear (GLM) and mixed linear (MLM) models for L. diplodia and N. parvum. Consensus genomic associations were identified in chromosome 12, position 10.60 Mb (Mi_0096) and 1 (Mango_rep_c1316) position 14.67 Mb, with association (P<0.0049) to L. theobromae loci, representing 20% ​​of the total variation. Additional regions identified on chromosomes 11 and 8 (positions 24.57 Mb and 9.34 Mb, respectively) by GLM and MLM explain 36% of the total variation for this disease. Consensus genomic associations were identified in chromosomes 2, position 20.49 Mb (Mango_rep_c9407) and 9, position 15.01 Mb (Mango_rep_c8984), with association (P<0.006) for N. parvum loci, representing 20.6% of resistance total for this fungus.